Trends in Primary and Secondary Education Completion Rates in Indonesia, 2019–2023: An Analysis of the COVID-19 Pandemic Impact - Rezkiawaty (Journal of Strategy and Transformation in Educational Management, 2025)
Education completion rates are key indicators of a country’s progress in achieving equitable access and quality learning outcomes. In Indonesia, disparities across regions and levels of schooling have long posed challenges to the goal of universal education, and the COVID-19 pandemic (2020–2022) further tested the resilience of the national education system through extended school closures and an abrupt shift to distance learning. This study analyzes the five-year trends (2019–2023) in primary and secondary education completion rates, identifies patterns of increase or stagnation, and examines how emergency education policies influenced these trends. Using a descriptive quantitative approach with official secondary data from Statistics Indonesia and the Ministry of Education, this research applies descriptive statistics and trend visualizations to reveal that completion rates increased at all levels. The primary level maintained the highest rates, rising from 93.8% in 2019 to 96.8% in 2023, while lower secondary rose from 84.0% to 89.6%, and upper secondary, historically the weakest point, improved from 59.0% to 65.8%, with the sharpest annual gain (+5.5%) at the peak of the pandemic. Year-on-year changes suggest that emergency measures such as flexible graduation requirements, distance learning support, and internet subsidies successfully mitigated dropout risks in the short term. However, the slowing gains after 2021 indicate that temporary policies must be followed by sustainable structural interventions to address persistent regional disparities and the digital divide.